Effects of environmental factors on the spatio-temporal patterns of bigeyes (Priacanthus spp.) in the northern South China Sea - Yang, Zi; Wang, Xuefeng; Zeng, Jiawei; Lin, Kun; Lyu, Shaoliang; Chen, Guobao (Indian Journal of Fisheries, 2021)
Bigeyes (Priacanthus spp.; Family: Priacanthidae) are among the most significant demersal fishes in northern South China Sea (nSCS). Based on the bottom trawl data of nSCS from 2009 to 2014, this study applied the SARIMA (Seasonal Autoregressive Integrated Moving Average) model and the centre of gravity movement to analyse the spatio-temporal patterns of catch per unit effort (CPUE). Combining with the corresponding environmental factors of each trawling cruise, including bottom water temperature (BWT), bottom water salinity (BWS) and sea surface height (SSH) and their relationships with the CPUE were analysed by generalised linear model (GLM). The results indicated that, the monthly CPUE varied in half a year as a period and the peak in the first half year was obviously lower than the one in the second half year. The annual temporal trend of the centre of gravity movement was similar, which was related to the monthly variation of CPUE. Among the environmental factors, SSH had the greatest impact on CPUE, especially in October, November and December, 2009 and 2012; BWS had a significant impact on CPUE in July, August and September, 2009 and October, November and December, 2012. The spatio-temporal scale of the CPUE was mainly influenced by SSH and BWS under the effect of nSCS currents. This study presents a method for spatio-temporal variation of economic fish CPUE, integrating the centre of gravity movement and the temporal variation of the CPUE with the environmental factors, which is helpful for determining the fishery management unit and closed fishing season in the nSCS.Keywords: Bigeye fish (Priacanthus spp.), Environmental factors, Generalised linear model (GLM), Northern South China Sea (nSCS), Spatio-temporal patterns